(untitled) (Journal of Applied Business and Technology, 2023)
This study aims to criticize the income account contained in Pesantren Accounting Guidelines (Pedoman Akuntansi Pesantren / PAP). The critical paradigm is used as an “umbrella” for research with critical analysis as a research method. The results of this study indicate that (1) The definition of income in PAP and income in business entities is “almost” the same. (2) Making the contribution of santri as one of the free incomes is an inappropriate policy because santri are not a commodity.